Bugis local wisdom in the housing and settlement form: An architectural anthropology study - A. Akil; W. W. Osman (Lowland Technology International, 2017)
This study discusses the Bugis local wisdom in the housing and settlements form as part of efforts to strengthen the nation character. This study aims to discover the manifestation of Bugis cultural values in the housing and settlement form. Nowadays, It is considered important in effort to realize the planning and design of housing and settlements based on culture that can meet needs of life quality. This study is a qualitative research method that uses anthropologicalarchitecture by looking at the information units in the culture form and its relevance to the realization of housing and settlements. The data collected both qualitative and visual spatial, and then analyzed using Spradley through in-depth interviews, observation, and literature review. This study found that local wisdom of Bugis community are loaded with symbolicphilosophical meaning, among others: Bugis cultural values to the modern era is still alive; the values of Siri’, Were, and Pesse are based on the siri' na pesse value has manifested in the housing and settlements form, includes typical form of settlement space patterns, street patterns, building orientation, building form, commercial building form, and building layout.